Parental values about participation in physical activity by their children with disability - Abdul Malek , Siti Khadijah; Abdul Malek, Nur Ain; Abdul Malek, Nur Izzah; Abdul Malek , Nur Hanisah (Journal of Islamic, Social, Economics and Development, 2024)
The purposes of this study were to examine parental values about participation in physical activity by children with disabilities. The main focus of parental values was the influence of disability- related factors and demographics on parent’s perceptions of likely benefits and important benefits related to physical activity participation by their children with disabilities. The hypothesized correlates of children’s physical activity included parental values, children’s age and children’s gender groups. Questionnaire on Physical Activity Values Survey was distributed to 262 parents to obtain information about their perceptions of physical activity benefits, physical activity participation, disability information, and demographics. Overall, parents of children with disabilities seem knowledgeable about physical activity benefits and value their children’s participation in physical activity. The results of one way-ANOVA revealed that there was no significant main effect of children’s age and of children’s gender groups on likely benefits and important benefits of parental values. Overall, parental values were rated relatively high. This study provides valuable information about parental influence on physical activity participation by children with disabilities to several stakeholders, special school management.